2020
DOI: 10.1136/bmjopen-2019-036578
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases are the leading cause of mortality in rural Birbhum, West Bengal, India: a sex-stratified analysis of verbal autopsies from a prospective cohort, 2012–2017

Abstract: ObjectivesThere is a dearth of data on causes of death in rural India, which impedes identification of public health priorities to guide health interventions. This study aims to offer insights from verbal autopsies, to understand the pattern and distribution of causes of death in a rural area of Birbhum District, West Bengal, India.DesignCauses of death data were retrieved from a prospective vital event surveillance system.SettingThe Birbhum Population Project, a Health and Demographic Surveillance System, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… 60 More than three quarters of the studies (32/42) were surveillance studies. 19 , 21 24 , 26 , 28 44 , 48 52 , 54 , 55 , 57 , 58 Of 39 studies that recorded the study setting, 19 39 , 41 55 , 57 , 59 , 60 18 covered rural populations, 26 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 44 , 48 50 , 52 , 53 , 55 six covered urban populations, 21 , 25 , 46 , 47 , 51 , 59 and 15 covered both rural and urban populations at the country level. 19 , 20 , 22 24 , 27 , 29 , 31 , 33 , 36 , 38 , 45 , 54 , 57 , 60 The number of verbal autopsy deaths reported across all ages ranged between studies from 515 to 22 535, 47 , 53 and 20 studies reported deaths by sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 More than three quarters of the studies (32/42) were surveillance studies. 19 , 21 24 , 26 , 28 44 , 48 52 , 54 , 55 , 57 , 58 Of 39 studies that recorded the study setting, 19 39 , 41 55 , 57 , 59 , 60 18 covered rural populations, 26 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 44 , 48 50 , 52 , 53 , 55 six covered urban populations, 21 , 25 , 46 , 47 , 51 , 59 and 15 covered both rural and urban populations at the country level. 19 , 20 , 22 24 , 27 , 29 , 31 , 33 , 36 , 38 , 45 , 54 , 57 , 60 The number of verbal autopsy deaths reported across all ages ranged between studies from 515 to 22 535, 47 , 53 and 20 studies reported deaths by sex.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 20 , 22 24 , 27 , 29 , 31 , 33 , 36 , 38 , 45 , 54 , 57 , 60 The number of verbal autopsy deaths reported across all ages ranged between studies from 515 to 22 535, 47 , 53 and 20 studies reported deaths by sex. 19 , 23 , 26 , 28 , 31 , 33 , 35 , 42 44 , 47 , 48 , 50 52 , 54 56 , 58 , 60 . Thirty-two studies reported the number of verbal autopsy deaths in people aged 15 years and above; this number ranged from 300 to 472 113.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, those seeking healthcare services may already have either greater awareness of the impact of their lifestyle decisions, such as diets, or better means to eat more nutritious foods. A second explanation is that given the growing rate of non-communicable diseases and their associated risk factors in rural India, many of which have been linked to diets [ 30 , 31 ], those who are reporting healthcare expenses may have medical recommendations to adhere to healthier diets.…”
Section: Discussionmentioning
confidence: 99%
“…The study area of BIRPOP represents nearly 16% of the total population of Birbhum district (as per the Census of India, 2011). Predominantly rural, the Birbhum district is recognized to have poor human development indicators by the NITI Aayog , an apex policy thinktank of the Government of India 34 . The primary objective of BIRPOP is to undertake research and gather evidence to inform the state- and national public health policies.…”
Section: Methodsmentioning
confidence: 99%